Chapter Le testimonianze autobiografiche dei lettori: un nuovo orizzonte per la ricerca storico-educativa tra fonti orali e archivi digitali - DATI, MONICA (Studies on Adult Learning and Education, 2022)
By focusing on the relationship between reading and autobiographical memory, this study aims to bring out the importance of oral sources for restoring and deepening themes of absolute pedagogical relevance linked to family education, children's literature, schooling, censorship and the condition of women. Through illustrating some online archives in the Anglo-Saxon area and the madeleineinbiblioteca.it project, the aim is to bring out a field of investigation for historical-educational research, still largely unexplored. This can be seen as the first step in a path that is going to be enriched and further developed in order to demonstrate how oral history can be used to reflect on reading, its multiple formative values and the various contexts in which it is practised.